Teaching business ethics to postgraduates Does it make a difference? An Australian viewpoint - Issa, Theodora; Pick, David (IADIS Press, 2010)
There is a growing trend to increase business schools’ attention to teach business ethics, nonetheless, scholars continue to be at odds as to whether teaching business ethics, especially at the post graduate level might help or even make a difference. Deriving from a quantitative core component with a qualitative supplementary component, the aim of this paper is to provide empirical evidence from Australia that teaching business ethics (BE567) to post graduate students makes a difference and in the long term generates a shift in students’ mind sets. Both qualitative and quantitative data were collected through different methods including questions at the beginning of the semester, reflection at the end of the semester with an informal feedback provided during the semester, which provide evidence of a shift in students’ mind sets.Nonetheless, this paper will derive from the anonymous teaching and unit evaluation system in use by Curtin University ‘eVALUAte’ from 162 post graduate students of business ethics over five semesters in two different campuses. The analysis of this data suggests that there is an appreciation of the topic of business ethics at the postgraduate level making a difference and ultimately bringing in a shift in students’ mind sets. Through their evaluations of the unit and teaching, students highlighted the importance of such a unit, and how learning about issues of ethical nature is of importance to them personally and to businesses in general, which provides an assurance that the unit outcomes have been achieved in transforming students mind sets.